Protocol: Faecal microbiota transfer in liver cancer to overcome resistance to atezolizumab/bevacizumab$da multicentre, randomised, placebo-controlled, double-blind phase II trial (the FLORA trial) - Rauber, Conrad; Roberti, Maria Paula; Vehreschild, Maria JGT; Tsakmaklis, Anastasia; Springfeld, Christoph; Teufel, Andreas; Ettrich, Thomas; Jochheim, Leonie; Kandulski, Arne; Missios, Pavlos; Mohr, Raphael; Reichart, Alexander; et al. (BMJ open, 2025)
Introduction Combined vascular endothelial growth factor/programmed death-ligand 1 blockade through atezolizumab/bevacizumab (A/B) is the current standard of care in advanced hepatocellular carcinoma (HCC). A/B substantially improved objective response rates compared with tyrosine kinase inhibitor sorafenib; however, a majority of patients will still not respond to A/B. Strong scientific rationale and emerging clinical data suggest that faecal microbiota transfer (FMT) may improve antitumour immune response on PD-(L)1 blockade. Early trials in melanoma with FMT and reinduction of immune checkpoint blockade (ICI) therapy in patients with anti-PD-1-refractory metastatic melanoma were reported in 2021 and demonstrated reinstatement of response to ICI therapy in many patients. Due to anatomical vicinity and the physiological relevance of the gut-liver axis, we hypothesise HCC to be a particularly attractive cancer entity to further assess a potential benefit of FMT in combination with ICI towards increased antitumour immunity. Additionally, HCC often occurs in patients with liver cirrhosis, where liver function is prognostically relevant. There is evidence that FMT may increase hepatic function and therefore could positively affect outcome in this patient population. - Methods and analysis This prospective, multicentre, randomised, placebo-controlled, double-blind phase II clinical trial has been designed to assess immunogenicity and safety of FMT via INTESTIFIX 001 combined with A/B in advanced HCC in comparison to A/B with placebo. Primary endpoints are measured as tumour CD8+ T cell infiltration after 2 cycles of treatment with vancomycin, A/B+INTESTIFIX 001 in comparison to vancomycin-placebo, A/B+INTESTIFIX 001-placebo and safety of the therapeutic combination in advanced HCC. INTESTIFIX 001 is an encapsulated FMT preparation by healthy donors with a high alpha-diversity in their gut microbiome for oral administration, manufactured by the Cologne Microbiota Bank (CMB). Sample size was calculated to achieve a specific expected accuracy for the primary immunological endpoint. 48 subjects will be randomised to reach a goal of 42 usable measurements in the modified intention-to-treat set. Subjects will be randomised in a 2:1 ratio to A/B or placebo (28 A/B, 14 placebo). - Ethics and dissemination The study was approved by ethics committee review and the German Federal Ministry of Drugs and Medical Devices. The trial is registered under EU CT no. 2023-506887-15-00. The outcome of the study will be disseminated via peer-reviewed publications and at international conferences. - Trial registration number NCT05690048.
Online veröffentlicht: 9. September 2025
Gesehen am 17.11.2025